Thermal analysis and entropy generation of magnetic Eyring-Powell nanofluid with viscous dissipation in a wavy asymmetric channel - Bhatti, M. M.; Sait, Sadiq M.; Ellahi, R.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi (Emerald Group Publishing Ltd, 2023)
PurposeThis study aims to deal with entropy generation and thermal analysis of magnetic hybrid nanofluid containing silver and gold as nanoparticles (Au-Ag/NPs) in the Eyring-Powell fluid. Design/methodology/approachThe blood is used as a base fluid to study the rheological effects in a wavy asymmetric channel. The effect of viscous dissipation is also taken into account. The mathematical model is developed using the lubrication technique. The perturbation method is used to solve the nondimensional nonlinear differential equations, whereas the pumping properties have been analyzed using numerical integration. FindingsThe impact of entropy generation, Brinkman number, Hartmann number, nanoparticles volume fraction, thermal Grashof number, Brinkman number and Eyring-Powell fluid parameter is examined on the velocity profile, temperature profile and pumping characteristics. It is observed that the introduction of gold and silver nanoparticles boosts the velocity field in a smaller segment of the channel. The temperature profile rises for the increasing values of Hartmann number, Brinkman number and nanoparticle volume fractions while the temperature profile is restrained by the Eyring-Powell fluid parameter. The pumping rate rises in all sections as the thermal Grashof number and Hartmann number increase; however, the Eyring-Powell fluid parameter has the reverse effect. The volume of the trapping boluses is significantly affected by the Eyring-Powell fluid parameter, thermal Grashof number and fluid parameter. Originality/valueThe results are original and contribute to discover the role of hybrid nanoparticles under the influence of entropy generation viscous dissipation and magnetic fields. Pharmaceutical technology may use this research for things like better mucoadhesive drug delivery systems and more productive peristaltic micropumps.
Keywords: Entropy analysis; Magnetohydrodynamics; Eyring-Powell fluid; Blood flow; Silver and gold nanoparticles; Lubrication theory; Viscous dissipation; MHD; Nanoparticles